WORK SHEET DEVELOPMENT (LKPD) BASED ON GUIDED DISCOVERY LEARNING MODEL FOR EXTRESSION SYSTEM MATERIALS IN CLASS VIII SMP / MTS - Puji Indriani; Lufri Lufri (Department of Science Education, 2021)
The 2013 curriculum is a refinement of the Education Unit Level curriculum (KTSP). The 2013 curriculum emphasizes the competencies that must be achieved are spiritual attitudes (KI-1), social attitudes (KI-2), and skills (KI-4). The 2013 curriculum uses a scientific approach, thus forming scientific behavior, social behavior and an attitude of curiosity. The teacher must take a variety of approaches so that the learning process takes place fun. LKPD teaching materials based on the Guided Discovery Learning model are used in the learning process because it can guide students in developing their own discovery concepts in a guided and directed way. Based on this research has been carried out with the aim of producing a LKPD based on a valid Guided Discovery Learning model. This research is a development study with a 4-D model which is only carried out up to 3 stages due to limitations, research is limited to the Define stage, design, Develop. The data collection instrument used was a validation questionnaire. The validation was carried out by 3 educational experts (lecturers) as the LKPD validator based on the Guided Discovery Learning model. Data were analyzed using descriptive statistics (percentages). The results showed that the average value of the validity of LKPD was 83.31% (valid category), both in terms of content worthiness, linguistic, presentation, and graphic. In this study practicality test was not carried out because all schools were closed and replaced with learning at home because of the co-19 pandemic so that researchers only carried out the validity stage.